Closed-loop auditory stimulation of slow-wave sleep in chronic insomnia: a pilot study - Dudysová, Daniela; Janků, Karolina; Piorecký, Marek; Hantáková, Veronika; Orendáčová, Mária; Piorecká, Václava; Štrobl, Jan; Kliková, Monika; Ngo, Hong-Viet V; Kopřivová, Jana (Journal of sleep research, 2024)
Insomnia is a prevalent and disabling condition whose treatment is not always effective. This pilot study explores the feasibility and effects of closed-loop auditory stimulation (CLAS) as a potential non-invasive intervention to improve sleep, its subjective quality, and memory consolidation in patients with insomnia. A total of 27 patients with chronic insomnia underwent a crossover, sham-controlled study with 2 nights of either CLAS or sham stimulation. Polysomnography was used to record sleep parameters, while questionnaires and a word-pair memory task were administered to assess subjective sleep quality and memory consolidation. The initial analyses included 17 patients who completed the study, met the inclusion criteria, and received CLAS. From those, 10 (58%) received only a small number of stimuli. In the remaining seven (41%) patients with sufficient CLAS, we evaluated the acute and whole-night effect on sleep. CLAS led to a significant immediate increase in slow oscillation (0.5-1 Hz) amplitude and activity, and reduced delta (1-4 Hz) and sigma/sleep spindle (12-15 Hz) activity during slow-wave sleep across the whole night. All these fundamental sleep rhythms are implicated in sleep-dependent memory consolidation. Yet, CLAS did not change sleep-dependent memory consolidation or sleep macrostructure characteristics, number of arousals, or subjective perception of sleep quality. Results showed CLAS to be feasible in patients with insomnia. However, a high variance in the efficacy of our automated stimulation approach suggests that further research is needed to optimise stimulation protocols to better unlock potential CLAS benefits for sleep structure and subjective sleep quality in such clinical settings.
Keywords: akustická stimulace; dospělí; průzkumy a dotazníky; Female; klinické křížové studie; Acoustic Stimulation; Adult; ženské pohlaví; Surveys and Questionnaires; Sleep, Slow-Wave; insomnia; lidé; polysomnografie; Pilot Projects; slow oscillation; kvalita spánku; pilotní projekty; Cross-Over Studies; poruchy iniciace a udržování spánku; Memory Consolidation; Polysomnography; memory consolidation; Male; Sleep Initiation and Maintenance Disorders; konsolidace paměti; spánek pomalých vln; closed‐loop auditory stimulation; lidé středního věku; polysomnography; mužské pohlaví; Sleep Quality; elektroencefalografie; Middle Aged; Electroencephalography; Humans